Multiple stressors determine river ecological status at the European scale: Towards an integrated understanding of river status deterioration. (19th February 2021) - Lemm, Jan U.; Venohr, Markus; Globevnik, Lidija; Stefanidis, Kostas; Panagopoulos, Yiannis; van Gils, Jos; Posthuma, Leo; Kristensen, Peter; Feld, Christian K.; Mahnkopf, Judith; Hering, Daniel; Birk, Sebastian
Abstract: The biota of European rivers are affected by a wide range of stressors impairing water quality and hydro‐morphology. Only about 40% of Europe's rivers reach 'good ecological status', a target set by the European Water Framework Directive (WFD) and indicated by the biota. It is yet unknown how the different stressors in concert impact ecological status and how the relationship between stressors and status differs between river types. We linked the intensity of seven stressors to recently measured ecological status data for more than 50, 000 sub‐catchment units (covering almost 80% of Europe's surface area), which were distributed among 12 broad river types. Stressor data were either derived from remote sensing data (extent of urban and agricultural land use in the riparian zone) or modelled (alteration of mean annual flow and of base flow, total phosphorous load, total nitrogen load and mixture toxic pressure, a composite metric for toxic substances), while data on ecological status were taken from national statutory reporting of the second WFD River Basin Management Plans for the years 2010–2015. We used Boosted Regression Trees to link ecological status to stressor intensities. The stressors explained on average 61% of deviance in ecological status for the 12 individual river types, with all seven stressors contributing considerably to this explanation. On average, 39.4% of the deviance was explained by altered hydro‐morphology (morphology: 23.2%; hydrology: 16.2%), 34.4% by nutrient enrichment and 26.2% by toxic substances. More than half of the total deviance was explained by stressor interaction, with nutrient enrichment and toxic substances interacting most frequently and strongly. Our results underline that the biota of all European river types are determined by co‐occurring and interacting multiple stressors, lending support to the conclusion that fundamental management strategies at the catchment scale are required to reach the ambitious objective of good ecological status of surface waters. Abstract : We analyzed the effects of multiple stressors on ecological status of more than 50, 000 European river catchments. Hydro‐morphological degradation showed the strongest effects, followed by nutrient enrichment and toxic substances. Interactive stressor effects were prominent. Our findings highlight the role of multiple stressors acting on Europe's rivers and call for fundamental restorative management strategies at the catchment‐scale.